Interfacial stresses in reinforced concrete cantilever members strengthened with fibre-reinforced polymer laminates. Issue 2 (January 2020) - He, Xue-jun; Zhou, Chao-Yang; Wang, Yi
Fibre-reinforced polymers have been increasingly used to strengthen reinforced concrete structures. However, premature brittle debonding failures may occur at the ends of externally bonded fibre-reinforced polymer laminates due to interfacial stress concentrations caused by stiffness imbalances. Although many studies exist on fibre-reinforced polymer-strengthened simply supported beams and slabs, the interfacial stress distributions in fibre-reinforced polymer-strengthened cantilever members are very different from those in simply supported members. Based on the assumptions of linear elasticity, deformation compatibility and static equilibrium conditions, the interfacial stresses in fibre-reinforced polymer-strengthened reinforced concrete cantilever members under arbitrary linear distributed loads were analysed. In particular, closed-form solutions were obtained to calculate the interfacial stresses under either a uniformly distributed load or a single concentrated load located at the overhanging end of the cantilever member. Existing test results on cantilever slabs strengthened by carbon fibre–reinforced polymer sheets were used to verify the model. According to the parametric analysis, the maximum interfacial stresses can be reduced by decreasing the fibre-reinforced polymer thickness, increasing the fibre-reinforced polymer bonding length and increasing the adhesive layer thickness, and by using less rigid fibre-reinforced polymer laminates with high tensile strengths. These results are useful for engineers seeking to optimize strengthening design parameters and implement reliable debonding prevention measures.